Phylogenetic and Functional Characterization of Culturable Endophytic Actinobacteria Associated With Camellia spp. for Growth Promotion in Commercial Tea Cultivars - Borah, Atlanta; Thakur, Debajit (Frontiers in Microbiology, 2020)
Plant associated endophytic actinobacteria may contribute to plant growth and defense by direct or indirect methods. Our aim was to evaluate the plant growth promoting and antifungal activities of endophytic actinobacteria associated with Camellia spp. and related genera, Eurya to find potent plant growth promoting strains that could be applied in future microbe based bioformulations. We isolated 46 endophytic actinobacteria based on morphological characteristics of the isolates. 16S rRNA gene sequence analysis showed that the strains represented nine actinobacterial genera, Nocardia, Amycolatopsis, Streptomyces, Pseudonocardia, Kribbella, Actinomadura, Microbispora, Rothia and Saccharomonospora. In vitro functional characterization of the strains for plant growth promoting (PGP) traits revealed many potent PGP isolates such, as SA1 and S43 which showed all the tested PGP traits, i.e. phosphate solubilization, indole-3-acetic acid (IAA), ammonia, siderophore and chitinase production. 21 isolates of the total 46 isolates, inhibited the growth of atleast one test fungal phytopathogen out of which, strains SA25 and SA29 exhibited broad spectrum antifungal activity against all the tested phytopathogens. Most of the endophytic actinobacteria isolates having antifungal activity were positive for the presence of chitinase, NRPS (Nonribosomal peptides synthetase) or PKS-1 (Polyketide Synthase) gene, suggesting the presence of distinctive mechanisms to inhibit the growth of pathogenic plant fungi. ARDRA (Amplified Ribosomal DNA Restriction analysis) and BOX-PCR fingerprinting analysis of the potent strains with antagonistic activity grouped the strains into 5 and 4 separate clusters, respectively. In addition, an assessment using bonitur scale revealed the top ranked isolates based on their PGP and biocontrol traits. Further detection of IAA production by the top ranked actinobacterial isolates namely, SA1, T1LA3 and S85 by using thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS) was done. Strains, SA1, T1LA3, and SA14 were further tested for their efficacy in promoting the growth of commercial tea clones, TV1, TV9, TV18, and TV22 in nursery conditions. All the endophytic isolates tested showed significant differences (P ≤ 0.05) in terms of plant growth promoting parameters in the treated plants compared to untreated control and may, thus be, deemed as potential candidates for application in bioformulations for tea growth.